A Novel Topical Combination Ointment with Antimicrobial Activity against Methicillin-Resistant Staphylococcus aureus, Gram-Negative Superbugs, Yeasts, and Dermatophytic Fungi - Kenneth S. Thomson, B.Ag.Sc, MS, PhD; Gina K. Thomson, MT; John Biehle, BS; Andrew Deeb, BS; Jamaal Crawford, BS; R. Herrera (Elsevier, 2016)
Background: The use of topical antimicrobial agents for management of minor skin infections is a clinical strategy that is commonly practiced in the community. Coupled with the use of topical antimicrobial agents is the emergence of antibiotic-resistant strains of pathogens leading to the need for alternative treatments. Objective: A novel topical combination ointment consisting of salicylic acid, oak bark extract, benzoic acid, and polyethylene glycol (Bensal HP, Sonar products Inc., Carlstadt, NJ) with antimicrobial properties was assessed to determine its spectrum of activity. Methods: One hundred eighty-four bacterial and fungal isolates from culture collections that included multidrug-resistant bacteria such as methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter spp, and gram-negative so-called superbugs, as well as yeasts and filamentous fungi, were investigated by cylinder diffusion and agar dilution assays. Results: All 184 bacterial and fungal isolates were susceptible to the combination ointment at the clinically applied concentration and there was no evidence of cross-resistance between Bensal HP and other classes of antimicrobials. In time-kill tests, Bensal HP was rapidly bactericidal against P aeruginosa ATCC 27853 and methicillin-resistant S aureus SA179 at 4 × the MIC, a concentration that is applied clinically. Conclusions: The results of this study suggest that this combination ointment has a broad in vitro spectrum of antimicrobial activity against both more common bacterial and fungal pathogens and may be particularly useful for treatment of infections by multidrug-resistant organisms. Additional studies are warranted to investigate the full clinical utility as a therapeutic agent and also for possible infection control interventions.